Institutions, Informality, and Wage Flexibility : Evidence From Brazil - de Carvalho Filho, Irineu (IMF Working Papers; Working Paper, 2012)
Even though institutions are created to protect workers, they may interfere with labor market functioning, raise unemployment, and end up being circumvented by informal contracts. This paper uses Brazilian microeconomic data to show that the institutional changes introduced by the 1988 Constitution lowered the sensitivity of real wages to changes in labor market slack and could have contributed to the ensuing higher rates of unemployment in the country. Moreover, the paper shows that states that faced higher increases in informality (i.e., illegal work contracts) following the introduction of the new Constitution tended to have smaller drops in wage responsiveness to macroeconomic conditions, thus suggesting that informality serves as a escape valve to an over-regulated environment.